Prevalence of pemphigus incidence in the Bhuj, Kutch, Gujarat: a cross-sectional study - Parmar, Devendra; Patel, Keyur J. (International Journal of Research in Dermatology, 2017)
Background: Pemphigus is a group of rare skin disorders that cause blisters and sores on the skin or mucous membranes, such as in the mouth or on the genitals. In Brazil, the prevalence of the disorder is 3.4% in regions such as the Amerindian reservation of Limão Verde and approximately 15,000 patients are known to have pemphigus foliaceus. This prompted us to conduct a study to estimate the incidence of pemphigus in the central Bhuj district of the state of Gujarat in India. Methods: The present study was planned and conducted between January 2016 to December 2016. The entire team of dermatologists licensed in the district were included in the study and full efforts were made to reach out to them. All the participating dermatologists were asked to fill up a simple perform prepared by the experts in the field. The Performa included the details like date, investigations required for pemphigus, diagnosis based for pemphigus. Results: The total population of Bhuj district is estimated to be 5 millions. At the end of the study period that is one year, all the collected performa from the licensed dermatologist were evaluated and results were prepared accordingly. A total of 24 patients who fulfilled all the inclusion criteria were included in the study. Conclusions: This original research proves that the incidence of pemphigus in Bhuj district was 7.2 per million in the period of one year. This incidence is much higher than the incidence rates reported from the Germany where only 14 cases were reported over a period of 8 years. This study does give us a preliminary idea about the incidence of this rare disease in this geographic area.